UJI KECEPATAN REKONSTRUKSI CITRA PADA CT-SCAN METODE BACK-PROJECTION (BP) DAN METODE FILTERED BACK-PROJECTION (FBP) DENGAN PEMFILTERAN PADA DOMAIN SPASIAL - Ngurah Sutapa, Gusti; Anam, Choirul (BERKALA FISIKA, 2011)
Conventional X-ray have many limitations in describing the object being imaged because of overlap on multiple objects on a single line of projection. To overcome this limitation, the object was expossed in several directions, and then the projections from several directions was reconstructed to get cross-section image. The reconstruction method was widely used filtered back projection method as the development of a simple back projection. In this study will be evaluated the speed of the reconstruction for the back projection method and filtered back projection in the spatial domain. It was conducted for the projection angle from 0 to 180 degree, with interval Â 25, 20, 15, 10 and 5 degrees. In this research the number pixels was 50x50. It was found that the smaller of the interval of the angle projections, then it will get better results, but it takes longer. From back projection and filtered back projection methods, was obtained if the interval of the angle projections a half times smaller, it will take nearly twice as long of time. It was found that the time difference between back-projection and filtered back projection methods is less than 0.1 seconds. Keywords: Image reconstruction, back-projection, filtered back-projection, convolution